(3CLhHI GdeSGFd GdYTQs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3SFd GdTjN GdYGde GHf SjfG eSGFd YTQI , aCLGH Yf GdLejY hgPg UhQJgG s
(3BNQgG (B:s
(3ef GdfaS hGdeYGdL ef GdHOf hGdaYd GdaGYd ai GdbGHd dCLd GdZGjI dJMUd GdUhQI JeJ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B238 - (3U(B241s
(3GfXQ eDdaGJ GHf SjfG dLhQL bfhGJi HQbe (B2s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B4 s
Keywords: (3GdWHs